Research on the geological process of river action on the toppling deformation of rocky bank slopes in V-shaped gorge reservoirs - Teng, Lin; Dong, Menglong; Xing, Xiansen; Xu, Yingze; Sun, Changze; Liu, Zujian; Yang, Kai (Frontiers in Earth Science, 2024)
The toppling deformation in bank slope of V-shaped Gorge reservoirs in Southwest China is very common. After the impoundment of the reservoir, geological disasters such as collapse and landslide may occur in toppling bank slope, which poses a threat to the normal operation of hydropower projects and personnel safety.Therefore, it is of great engineering significance to study its genetic mechanism and development law. The trenching of river valley is one of the main factors of bank slope toppling deformation. In the process of river action, the free face is formed on the slope, and the rock mass is unloaded to the free face, resulting in toppling. Taking the bank slope of a reservoir in the V-shaped Gorge area on the edge of the Qinghai Tibet Plateau in Southwest China as an example, this paper studies the relationship between river action and the development of toppling. According to the seven terraces formed on both banks of the river, the trenching of the river valley is divided into seven stages.The toppling development characteristics of each stage are analyzed by discrete element method. According to the development characteristics of toppling deformation category, the toppling deformation is divided into five stages, they are initial toppling deformation stage, toppling development stage, intensified toppling deformation stage, temporary stability stage and failure stage. The research results can help to determine the development type and stage of bank slope toppling deformation in V-shaped Gorge area, so as to predict its further development deformation characteristics.